The Good Fortune of Online Influencers - Mabie, Zoe (The IIE, 2015)
The introduction of the internet has created a whole new dimension of opportunity and connectivity for people around the world (DiMaggio, Hargittai, Neuman & Robinson, 2001). The number of peo-ple gaining access to and using the internet increased exponentially over time. In 1995 there were less than 20 000 live web sites on the internet, in under six years, it grew to over ten million (Di-Maggio et al. 2001). The internet allowed for people all over the world to not only communicate and share but to also converse and learn. It also created a new platform of communication for brands. Media, in a traditional sense has always involved press and television, now, brands are able to communicate to their audiences on a more personalised, specified level, talking directly and more promptly to conversations people are having about their brand. Brands started seeing this platform as an additional channel through which brands can speak to their audiences (DiMaggio et al. 2001). While big brands were developing strategies to talk to their audiences through the digital platform, another phenomenon was developing. The phenomenon of social media, where individuals all over the world were sharing and conversing about topics of interest as well as themselves, it became an opportunity for people to connect with each other and communicate without necessarily being in each other’s presence (Kietzmann, Hermkens, McCarthy & Silvestre, 2011). Social media gave users an opportunity to stay connected to each other without having to physically be in contact with each other; soon enough, activity on social media became a form of self-expression (Kietzmann et al. 2011). Never before was it this easy to communicate with individuals on a global platform, peo-ple in China where learning about and communicating with people in Brazil. People who had formed friendships from travelling the world, were able to stay in contact and maintain their friend-ships, the term globalisation had never been more relevant (Kietzmann et al. 2011). Social media was here to stay. Social media has changed the landscape of communication; it would only make sense to investigate the phenomenon’s that have arisen from it.
Keywords: Social Media; Online Influencers; Branding; Consumer Relationships